Quorum Sensing in Some Representative Species of Halomonadaceae - Tahrioui, Ali (MDPI, 2013)
Cell-to-cell communication, or quorum-sensing (QS), systems are employed by bacteria for promoting collective behaviour within a population. An analysis to detect QS signal molecules in 43 species of the Halomonadaceae family revealed that they produced N-acyl homoserine lactones (AHLs), which suggests that the QS system is widespread throughout this group of bacteria. Thin-layer chromatography (TLC) analysis of crude AHL extracts, using Agrobacterium tumefaciens NTL4 (pZLR4) as biosensor strain, resulted in different profiles, which were not related to the various habitats of the species in question. To confirm AHL production in the Halomonadaceae species, PCR and DNA sequencing approaches were used to study the distribution of the luxI-type synthase gene. Phylogenetic analysis using sequence data revealed that 29 of the species studied contained a LuxI homolog. Phylogenetic analysis showed that sequences from Halomonadaceae species grouped together and were distinct from other members of the Gammaproteobacteria and also from species belonging to the Alphaproteobacteria and Betaproteobacteria.